Prevelance Study Of Celiac Disease(Cd) In Type 1 Diabetes Patients - ماضي, ماهر; سلمان, ربا; غصه , علي (Latakia University Journal -Medical Sciences Series, 2022)
Background : : Celiac disease is relatively common chronic disease(1_2%) of the world's population, and can be present at any age. It's an autoimmune disease such as Type 1 diabetes. Early diagnosis of celiac disease in type 1 diabetes patients protects against irreversible complications such as growth failure and short suture and helps control blood sugar and prevent complications. Patients and Methods : we conducted a cross sectional study to investigate celiac disease in patients with type 1 diabetes who attended Tishreen University Hospital in Lattakia for a year between 2020-2021 after obtaining the approval. The study included 81 patients with type 1 diabetes according to the entry criteria. A blood analysis was performed for all patients included anti ttg igA, total igA, glucose, calcium, hemoglobin and albumin, with a detailed clinical history of digestive symptoms taken. Results : The prevalence of celiac disease among patients with type 1 diabetes in our study which included 81 patients, reached 9.8%, which is in agreement with the rates in the reference studies that ranged between 5.5% and 10.4%, and above the global rates for the prevalence of celiac disease in the general population. It was also found that it is not possible to rely on clinical symptoms to determine who are the patients with type 1 diabetes who should be investigated for celiac disease. Conclusion : Early detection of celiac disease should be done in all patients with type 1 diabetes, regardless of clinical symptoms or laboratory values, because early detiction of associated celiac disease protects against irreversible complications .